2009
DOI: 10.1073/pnas.0903427106
|View full text |Cite
|
Sign up to set email alerts
|

Differential neutralization efficiency of hemagglutinin epitopes, antibody interference, and the design of influenza vaccines

Abstract: It is generally assumed that amino acid mutations in the surface protein, hemagglutinin (HA), of influenza viruses allow these viruses to circumvent neutralization by antibodies induced during infection. However, empirical data on circulating influenza viruses show that certain amino acid changes to HA actually increase the efficiency of neutralization of the mutated virus by antibodies raised against the parent virus. Here, we suggest that this surprising increase in neutralization efficiency after HA mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
103
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 24 publications
9
103
0
Order By: Relevance
“…This was, however, observed for two positions of the HA and NA segments. Position 215 of HA is a previously established antibody binding site within the antigenic epitope D of influenza virus and has also been described as a part of a human T cell epitope [60, 61]. In NA, position 151 has been shown to play a role in catalytic activities and receptor binding properties of the virus, as well as drug susceptibility to zanamivir [62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…This was, however, observed for two positions of the HA and NA segments. Position 215 of HA is a previously established antibody binding site within the antigenic epitope D of influenza virus and has also been described as a part of a human T cell epitope [60, 61]. In NA, position 151 has been shown to play a role in catalytic activities and receptor binding properties of the virus, as well as drug susceptibility to zanamivir [62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…Our proposed computational model identified 39 antigenicity-associated sites, with the dominant sites determining the antigenic drift events from 1968 to 2007. Ndifon et al (30) presented a competitive model to predict antibody escape, proposing that antigenic drift events would be associated with amino acid changes that occur in epitopes with high neutralization efficiencies (i.e., epitopes A, B, and D) rather than in those with low neutralization efficiencies (i.e., epitopes C and E). Supporting this prediction, the major residues our algorithm identified are in epitopes A and B.…”
Section: Discussionmentioning
confidence: 99%
“…Epitopes on the globular head of the influenza haemagglutinin are more accessible and thus more immunogenic than epitopes on the recessed stalk, potentially explaining the preponderance of antibodies to the head despite broader protection associated with anti-stalk antibodies [121]. It has been speculated that influenza may evolve immunogenic decoy epitopes, far from neutralizing epitopes, that may sterically interfere with neutralizing antibodies [122]. Pauli et al [120] observed that most anti-SpA antibodies in their experiments derived from the IGVH3 idiotype, which suggests that epitopes' immunogenicity might account for not only the phenotypic but also the genotypic diversity of the repertoire.…”
Section: Growth and Competition Among The Clonesmentioning
confidence: 99%